Inflation Targeting and Exchange Rate Rules in an Open Economy - Parrado, Eric (IMF Working Papers; Working Paper ;, 2004)
This paper provides a simple dynamic neo-Keynesian model that can be used to analyze the impact of monetary policy that considers inflation targeting in a small open economy. This economy is characterized by imperfect competition and short-run price rigidity. The main findings of the paper are that, depending on what shocks affect the economy, the effects of inflation targeting on output and inflation volatility depend crucially on the exchange rate regime and the inflation index being targeted. First, in the presence of real shocks, flexible exchange rates dominate managed exchange rates, while for nominal shocks the reverse is true. Second, domestically generated inflation targeting is preferable to CPI inflation targeting, because the former is more stabilizing not only in relation to both measures of inflation, but also to the output gap and the real exchange rate. Finally, flexible inflation targeting outperforms strict inflation targeting in terms of welfare.